The Impact of Enhancing Religious Moderation on the Economic Development of the Modongan Village in the Mojokerto Regency - Zuana, Muhammad Mujtaba Mitra; Isbahi, Muhammad Baiqun; Toha, Mohamad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The objective of this study is to examine the promotion of religious moderation and its relationship with socioeconomic advancement. The current study utilized a qualitative research methodology, specifically employing a case study design. The current investigation was conducted in the Modongan Village of the Mojokerto Regency. The incumbent occupies the role of Chief of Villages and Religious Leaders in the Modongan Village. The data collection methods utilized in this study included several techniques such as observation, interviews, recording, and focus group discussions (FGDs). The study's findings indicate that the endeavors to improve and enforce religious moderation in Modongan Village have achieved success up to this point. The community, religious leaders, and the Village Government have cooperated to ensure a balanced and fair implementation of values and teachings. The principles of their respective religions. The economic facilities and infrastructure in the Modongan Village are currently limited in both their size and ability. To address the dependence of a substantial percentage of the population on the agriculture sector for their livelihoods, the Village Government, Community/Religious Leaders, and the local community have started protecting agricultural land in the Modongan Village. The goal is to improve the quality of life for the population by following applicable laws and regulations, and by promoting environmental sustainability.